Modeling Accuracy and Variability of Motor Timing in Treated and Untreated Parkinson’s Disease and Healthy Controls - Jones, Catherine R.; Claassen, Daniel; Yu, Minhong; Spies, Jeffrey R.; Malone, Tim; Dirnberger, Georg; Jahanshahi, Marjan; Kubovy, Michael (Frontiers in Integrative Neuroscience, 2011)
Parkinson’s disease (PD) is characterised by difficulty with the timing of movements. Data collected using the synchronization-continuation paradigm, an established motor timing paradigm, have produced varying results but with most studies finding impairment. Some of this inconsistency comes from variation in the medication state tested, in the inter-stimulus intervals (ISI) selected, and in changeable focus on either the synchronization (tapping in time with a tone) or continuation (maintaining the rhythm in the absence of the tone) phase. We sought to re-visit the paradigm by testing across four groups of participants: healthy controls, medication naïve de novo PD patients, and treated PD patients both ‘on’ and ‘off’ dopaminergic medication. Four finger tapping intervals (ISI) were used: 250ms, 500ms, 1000ms and 2000ms. Categorical predictors (group, ISI, and phase) were used to predict accuracy and variability using a linear mixed model. Accuracy was defined as the relative error of a tap, and variability as the deviation of the participant’s tap from group predicted relative error. Our primary finding is that the treated PD group (PD patients ‘on’ and ‘off’ dopaminergic therapy) showed a significantly different pattern of accuracy compared to the de novo group and the healthy controls at the 250ms interval. At this interval, the treated PD patients performed ‘ahead’ of the beat whilst the other groups performed ‘behind’ the beat. We speculate that this ‘hastening’ relates to the clinical phenomenon of motor festination. Across all groups, variability was smallest for both phases at the 500 ms interval, suggesting an innate preference for finger tapping within this range. Tapping variability for the two phases became increasingly divergent at the longer intervals, with worse performance in the continuation phase. The data suggest that patients with PD can be best discriminated from healthy controls on measures of motor timing accuracy, rather than variability.